Production of hydrogen, active zerovalent iron and ferroferric oxide octahedron by alkaline etching Al–Fe alloys - Zheng, Tong; Li, Mingcong; Chao, Jingbo; Zhang, Jingqi; Tang, Yang; Wan, Pingyu; Hu, Qing; Coulon, Frederic; Bardos, Paul (Elsevier, 2021)
Hydrogen is becoming important clean energy while zerovalent iron (ZVI) and ferroferric oxide are of great interest to many applications including environmental remediation and chemical catalysis. Here, we report production of hydrogen, zerovalent iron and ferroferric oxide octahedron by etching Al–Fe alloys using NaOH solutions. The rate of hydrogen generation increased with increasing NaOH concentration and the alloy's particle size and decreasing the alloy's Fe concentration. Alkaline etching Al–Fe alloy particles of 425–850 μm produced 19–53 μm ZVI particles, which had paralleled ravines of 0.2–0.3 μm wide on the surface and possessed specific surface areas of 30–70 m2/g. The microscale ZVI was highly active for the removal of a model pollutant acid orange 7 from water. After 3–6 h ageing in the alkaline etching solution, the microscale ZVI particles were transformed to octahedral ferroferric oxide with saturation magnetization of 68.2 emu/g and residual magnetization of 13.2 emu/g and a coercive force of 330 Oe. This study provides a new approach for a facile synthesis of highly active ZVI and octahedral ferroferric oxide along with on-board generation of hydrogen from Al–Fe alloys.
Keywords: Water treatment; Ferroferric oxide octahedron; Al–Fe alloys; Hydrogen